The IMF and capital account liberalization: a case of failed norm institutionalization (2010)
While virtually all elements of the original agenda of the ‘Washington Consensus’ have become global policy norms over the course of the past twenty years, the case of free capital mobility stands out as an outlier. In his original formulation of the ‘to-do-list’ for economic reformers, John Williamson deliberately did not include capital account liberalization since he felt that no consensus could be reached in the late 1980s regarding its inclusion in the neoliberal reform package for developing countries (Williamson 1990). Yet capital account liberalization did become associated with the original Washington Consensus and even without formal validity reached the stage of norm emergence. A major driving force behind making capital mobility a policy norm was the International Monetary Fund (henceforth, the IMF or the Fund). However, despite strong support among the international financial institutions and the major powers in the global economic system, the unrestricted movement of international capital failed to leave the stage of norm emergence and to become a stabilized norm in the international financial system. In order to account for this outcome, we trace the evolution of the IMF's thinking on capital account liberalization from the early 1990s to the present. Specifically, we review the Fund's initial position on the benefits of liberalization, defined in terms of economic growth and market discipline. In doing so, we argue that the IMF has progressively reinterpreted the norm in terms of its allegedly welfare-enhancing effects, shifting from considering capital account liberalization as one of the essential variables that explain economic growth, to questioning this logic, to then highlight the positive alongside the negative effects of free capital mobility for developing countries.